RETRACTED: Extracellular Vesicles Long Non-Coding RNA AGAP2-AS1 Contributes to Cervical Cancer Cell Proliferation Through Regulating the miR-3064-5p/SIRT1 Axis - Li, Min; Wang, Jing; Ma, Hongli; Gao, Li; Zhao, Kunxiang; Huang, Tingting (Frontiers in Oncology, 2021)
Cervical cancer is one of the most severe and prevalent female malignancies and a global health issue. The molecular mechanisms underlying cervical cancer development are poorly investigated. As a type of extracellular membrane vesicles, EVs from cancer cells are involved in cancer progression by delivering regulatory factors, such as proteins, microRNAs (miRNAs), and long non-coding RNAs (lncRNAs). In this study, we identified an innovative function of extracellular vesicle (EV) lncRNA AGAP2-AS1 in regulating cervical cancer cell proliferation. The EVs were isolated from the cervical cancer cells and were observed by transmission electron microscopy (TEM) and were confirmed by analyzing exosome markers. The depletion of AGAP2-AS1 by siRNA significantly reduced its expression in the exosomes from cervical cancer and in the cervical cancer treated with AGAP2-AS1-knockdown exosomes. The expression of AGAP2-AS1 was elevated in the clinical cervical cancer tissues compared with the adjacent normal tissues. The depletion of EV AGAP2-AS1 reduced cell viabilities and Edu-positive cervical cancer cells, while it enhanced cervical cancer cell apoptosis. Tumorigenicity analysis in nude mice showed that the silencing of EV AGAP2-AS1 attenuated cervical cancer cell growth in vivo. Regarding the mechanism, we identified that AGAP2-AS1 increased SIRT1 expression by sponging miR-3064-5p in cervical cancer cells. The overexpression of SIRT1 or the inhibition of miR-3064-5p reversed EV AGAP2-AS1 depletion-inhibited cancer cell proliferation in vitro. Consequently, we concluded that EV lncRNA AGAP2-AS1 contributed to cervical cancer cell proliferation through regulating the miR-3064-5p/SIRT1 axis. The clinical values of EV lncRNA AGAP2-AS1 and miR-3064-5p deserve to be explored in cervical cancer diagnosis and treatments.